Synthesis of LaF 3 inorganic nanoparticles: Er 3+ , Yb 3+ by the coprecipitation method and characterization by optical spectroscopy and electron microscopy - Luis Acosta A. (2018)
This research was possible thanks to the support of CONCYTEC- Peru, agreement No. 167 FONDECYT-UNI and the Faculty of Sciences of the National University of Engineering, Peru. The spectra of absorption, fluorescence and electron microscopy were obtained thanks to the collaboration with the IFUNAM of Mexico. The high resolution electronic microscopy images were obtained thanks to the collaboration with University of Sonora, Mexico.